METHODOLOGICAL ASPECTS OF ASSESSING ANTHROPOGENIC LOAD ON THE UNDERGROUND HYDROSPHERE BY EXAMPLE OF KHERSON REGION - Scherbak, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In this paper the problem of groundwater degradation under the effect of anthropogenic activities was described. Special attention is paid to the application of quantitative criteria and GIS-technology to study the space-time features of change the anthropogenic load on underground hydrosphere. The methodological approach was proposed to analyze this process in regional scale by example of Kherson region.